Structure−Activity Relationships for Cytotoxic Ruthenium(II) Arene Complexes Containing N,N-, N,O-, and O,O-Chelating Ligands - Habtemariam, Abraha; Melchart, Michael; Fernández, Rafael; Parsons, Simon; Oswald, Iain D. H; Parkin, Andrew; Fabbiani, Francesca P. A; Davidson, James E; Dawson, Alice; Aird, Rhona E; Jodrell, Duncan I; Sadler, Peter J (Journal of medicinal chemistry, 2006)
We report structure−activity relationships for organometallic RuII complexes of the type [(η6-arene)Ru(XY)Cl]Z, where XY is an N,N- (diamine), N,O- (e.g., amino acidate), or O,O- (e.g., β-diketonate) chelating ligand, the arene ranges from benzene derivatives to fused polycyclic hydrocarbons, and Z is usually PF6. The X-ray structures of 13 complexes are reported. All have the characteristic “piano-stool” geometry. The complexes most active toward A2780 human ovarian cancer cells contained XY = ethylenediamine (en) and extended polycyclic arenes. Complexes with polar substituents on the arene or XY = bipyridyl derivatives exhibited reduced activity. The activity of the O,O-chelated complexes depended strongly on the substituents and on the arene. For arene = p-cymene, XY = amino acidate complexes were inactive. Complexes were not cross-resistant with cisplatin, and cross-resistance to Adriamycin was circumvented by replacing XY = en with 1,2-phenylenediamine. Some complexes were also active against colon, pancreatic, and lung cancer cells.